2005
DOI: 10.1111/j.1745-7262.2005.00006.x
|View full text |Cite
|
Sign up to set email alerts
|

Lepidium meyenii (Maca) reduces spermatogenic damage induced by a single dose of malathion in mice

Abstract: Maca enhances spermatogenesis following spermatogenic damage caused by the organophosphorous pesticide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 17 publications
4
32
1
2
Order By: Relevance
“…L. meyenii has been shown to enhance libido and fertility by modulating the hypothalamus-pituitary axis, regulating hormone secretion, and regulating interaction between the glucosinolates and androgen receptor (AR) [51]. There is also improvement of epididymal sperm count [52] and daily sperm production in the rat [53], as well as protection of sperm vitality against some noxious agents such as reduced air oxygen saturation [54] or toxic agents [55,56]. In a study on nine young adults to evaluate the effect of a 4-month oral treatment with Maca tablets (1,500 or 3,000 mg/d) on seminal analysis, the authors observed a significantly increased seminal volume, sperm count per ejaculum, motile sperm count, and sperm motility without modification in sexual hormone serum level [57].…”
Section: Lepidium Meyenii (Maca)mentioning
confidence: 97%
“…L. meyenii has been shown to enhance libido and fertility by modulating the hypothalamus-pituitary axis, regulating hormone secretion, and regulating interaction between the glucosinolates and androgen receptor (AR) [51]. There is also improvement of epididymal sperm count [52] and daily sperm production in the rat [53], as well as protection of sperm vitality against some noxious agents such as reduced air oxygen saturation [54] or toxic agents [55,56]. In a study on nine young adults to evaluate the effect of a 4-month oral treatment with Maca tablets (1,500 or 3,000 mg/d) on seminal analysis, the authors observed a significantly increased seminal volume, sperm count per ejaculum, motile sperm count, and sperm motility without modification in sexual hormone serum level [57].…”
Section: Lepidium Meyenii (Maca)mentioning
confidence: 97%
“…In 2001, maca was reported to increase sperm count in men [20]. Sperm Count: Scientific studies have shown that maca may increase daily sperm production (DSP), epididymal sperm count or vas deferens sperm count in both healthy rats [20,21] or when spermatogenesis was disturbed by different experimentally-induced abnormal conditions such as exposure to high altitude [22], injection of malathion [23], or administration of lead acetate [24].…”
Section: Male Reproductionmentioning
confidence: 99%
“…It also induct an increase in testis size and stimulation of spermatogenesis in rats and mice (Cicero et al, 2001;Gonzales et al, 200lb;Cicero et al, 2002). Maca reduced spermatogenic damage in mice and prostate size in rats (Bustos-Obregon et al, 2005;Gonzales et al, 2005), restored homeostasis impaired by restraint stress in mice (López-Fanso et al, 2004), and improved growth rate and survival in rainbow trout (Lee K. J. et al, 2004(Lee K. J. et al, , 2005. In adult men, increases in sexual desire, sperm volume, total sperm count, and sperm motility were observed, but serum biochemical parameters-except for reproductive hormones-were not evaluated (Gonzales et al, 2001a(Gonzales et al, , 2002(Gonzales et al, , 2003a.…”
Section: Discussionmentioning
confidence: 94%